Španělská chřipka v Čechách perspektivou úmrtních matrik v letech 1910-1925 - Kopecká, Tereza (Český časopis historický (Prague, Czech Republic : 1990), 2025)
The Spanish flu pandemic hit Prague in the autumn of 1918, killing thousands. With World War I ending and the collapse of the Austro-Hungarian Empire, the least favourable conditions for its peaceful management and thorough documentation had been created. The result of these circumstances is a number of questions that we will probably never answer, because the impact of war and pandemic on society is very difficult to distinguish. The regional specificity of the course of the pandemic and its experience is enormous. The death register of the General Hospital in Prague can help to clarify some questions related to Prague and Bohemia. To be able to distinguish the impact of war and pandemic as best as possible, this study expanded its interest to the years 1910–1925 and specifically monitored the prewar, war, flu, and post-flu conditions. Based on the data provided in the registers, it points to social factors that probably influenced the course and experience of the Spanish flu.